(515) محاضرات في النظام النقدي الدولي Lectures on the International Monetary System - محمد علي الجارحي (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة تطور وأبعاد "النظام النقدي الدولي"، حيث تستعرض ظاهرة النقود كأحد أعقد الظواهر الاقتصادية وأسرعها تغيراً. يهدف البحث إلى تصحيح المفاهيم الشائعة حول وظائف النقود (كمعيار للقيمة، ومستودع للثروة، ووسيلة للتبادل)، مع تحليل دقيق لكيفية تحديد أسعار صرف العملات الأجنبية بناءً على نظريات "تعادل القوة الشرائية" وقوى العرض والطلب الناتجة عن حركة التجارة الدولية، موضحاً بالرسوم البيانية والنماذج الرياضية كيفية اشتقاق منحنيات الطلب والعرض للعملات وعلاقتها بصادرات وواردات الدول، كما يحلل الملف آليات التوازن والاختلال في ظل النظم النقدية المختلفة، بدءاً من نظام الذهب (الكامل وغير الكامل) وصولاً إلى نظام الصرف المقيد الذي يشرف عليه صندوق النقد الدولي. ويناقش البحث بعمق أدوات التمويل الدولي (كخطابات الائتمان والسندات المصرفية) وعمليات "المقابلة" (Arbitrage) والتغطية في الأسواق المستقبلية للحد من مخاطر تقلب الأسعار. ويختتم البحث بتقييم فاعلية السياسات المالية والنقدية (كضغط الإنفاق وتعديل أسعار الصرف) في علاج عجز موازين المدفوعات، مؤكداً على التحدي المستمر في التوفيق بين أهداف الاستقرار الداخلي والتوازن الخارجي في ظل النظام النقدي العالمي المعاصر. This paper examines the evolution and dimensions of the "international monetary system," exploring money as one of the most complex and rapidly changing economic phenomena. It aims to correct common misconceptions about the functions of money (as a standard of value, a store of wealth, and a medium of exchange), while providing a detailed analysis of how foreign exchange rates are determined based on theories of purchasing power parity and the forces of supply and demand resulting from international trade. The paper uses graphs and mathematical models to illustrate how supply and demand curves for currencies are derived and their relationship to countries' exports and imports. It also analyzes the mechanisms of equilibrium and imbalance under different monetary systems, from the gold standard (complete and incomplete) to the fixed exchange rate system overseen by the International Monetary Fund. The paper discusses in depth international financing instruments (such as letters of credit and bank bonds), arbitrage, and hedging in futures markets to mitigate the risks of price volatility. The research concludes by assessing the effectiveness of fiscal and monetary policies (such as spending cuts and exchange rate adjustments) in addressing balance of payments deficits, emphasizing the ongoing challenge of reconciling the objectives of domestic stability and external balance within the contemporary global monetary system.